Coumarin–dihydropyrimidinone hybrids as promising agents against ovarian cancer: synthesis, SAR, and in silico evaluation - Santos, Jhonathan dos; Martinez, Alice; Abe, Saulo Henrique Mendes; Mello, Marcos Vinícius Palmeira de; Santos, João Pedro Araujo dos; Rodrigues, Carlos Rangel; Souza, Alessandra Mendonça Teles de; Batista, Alzir Azevedo; Corrêa, Arlene (Universidade Federal de São Carlos, 2026)
The coumarin scaffold is widely recognized for its broad range of biological activities, including antibacterial, anti-HIV, and anticancer properties. In parallel, molecular hybridization has emerged as an effective strategy to enhance biological activity and expand chemical diversity within drug discovery libraries. In this study, a series of coumarin–dihydropyrimidinone (DHPM) hybrids were synthesized via a Biginelli multicomponent reaction. The in vitro cytotoxic activity of these compounds was evaluated against a panel of cancer cell lines. A structure–activity relationship (SAR) analysis was carried out to elucidate the influence of different substituents and physicochemical properties on anticancer activity. Among the synthesized compounds, LSPN925 emerged as a good anticancer candidate and was further investigated for its effects on cell morphology and colony formation. In addition, in silico pharmacokinetic and toxicological evaluations were performed for the most active compounds to predict their drug-likeness and safety profiles. The preliminary SAR analysis revealed that lipophilicity and molecular volume of the compounds play a critical role in modulating their cytotoxic activity, highlighting these parameters as key considerations in the rational design of new coumarin-based anticancer agents. Overall, these findings support the potential of coumarin–DHPM hybrids as promising scaffolds for further anticancer drug development.
Keywords: 3,4-dihydropyrimidin-2(1H)-one; Coumarin; Molecular hybridization; Cancer; SAR; CIENCIAS EXATAS E DA TERRA::QUIMICA; 3. Saúde e Bem-Estar